A comparison of practice pattern and outcome of twice-weekly and thrice-weekly hemodialysis patients - T Mukherjee (Indian Journal of Nephrology, 2017)
Renal replacement therapy (RRT) options and practice varies in countries worldwide and is influenced by patients' choice, nephrologists' practice patterns, health system, payer practice, public policy, and socioeconomic factors. In India, hemodialysis (HD) remains the dominant RRT modality, and the practice is largely influenced by socioeconomics of the region of practice since third party payer is limited. Resource stretch to maximize outcome benefit is essential and HD session twice weekly is an improvized and cost-effective clinical practice. However, within the country, the patient characteristics, practice patterns, and outcomes of twice-weekly HD compared against patients dialyzed thrice weekly remain unclear. We did a retrospective analysis of patients who underwent twice- and thrice-weekly HD in a single center under similar settings. The patients on thrice a week dialysis were older and with a higher proportion of diabetics and were insured by private payers. Weight gain, ultrafiltration rates, blood pressures, and hemoglobin remained more favorable in the thrice-weekly patients. There was no significant difference in the hospitalization rates or mortality rates in the two groups. Patients who undergo twice-weekly HD have poorer intermediate measures of the outcome; although, morbidity and survival were not different in a small study population with short follow-up. The small sample size and the short duration of follow-up may limit the scope of findings of our study.